Research progress on abrocitinib in the treatment of moderate and severe atopic dermatitis - Xu ZHU; Wenzhong WU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Atopic dermatitis (AD) is an inflammatory skin disease characterized by pruritus. The efficacy of traditional treatment for moderate and severe AD is not satisfactory. AD has complex and multi-factor pathophysiological mechanisms.JAK-STAT pathway plays an important role in the pathogenesis of AD. Abrocitinib is a highly selective oral inhibitor of janus kinase 1 (JAK1), which can inhibit JAK-STAT signal transduction and activation pathways, resulting in down-regulation of the expression of IL-4, IL-13 and IL-31, which all are involved in the pathogenesis of AD, and ultimately blocks the occurrence and the development of AD. Abrocitinib has shown a good efficacy, tolerability and safety in the treatment of refractory moderate to severe AD. This article reviews the pharmacological mechanisms, clinical efficacy, safety and clinical applications of abrocitinib.